2020
DOI: 10.1111/josh.12907
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Health Literacy Into Core Curriculum: A Teacher‐Driven Pilot Initiative for Second Graders

Abstract: BACKGROUNDLimited research has addressed the effects of health literacy interventions in elementary schools. However, school‐aged children's health literacy is critical because children make decisions about their health every day. The purpose of the pilot project was to explore the feasibility of integrated health literacy lesson plans for second graders.METHODSA pretest‐posttest evaluation was conducted with second grade students following implementation of health literacy lessons that were integrated into co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…73 This shift may have been facilitated by the increasing use of age-specific measurement tools, such as pictorial tools and artifacts. [74][75][76][77] We also observed that indirect outcome ascertainment, using teacher and caregiver report rather than student report, was more common in interventions targeting students in K-2. This may be due to younger students' perceived reading and writing abilities; however, some studies used verbal surveys or other novel methods, such as artifact creation or pictorial questionnaires, to overcome this barrier.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…73 This shift may have been facilitated by the increasing use of age-specific measurement tools, such as pictorial tools and artifacts. [74][75][76][77] We also observed that indirect outcome ascertainment, using teacher and caregiver report rather than student report, was more common in interventions targeting students in K-2. This may be due to younger students' perceived reading and writing abilities; however, some studies used verbal surveys or other novel methods, such as artifact creation or pictorial questionnaires, to overcome this barrier.…”
Section: Discussionmentioning
confidence: 66%
“…This demonstrated that even in younger children it is possible to measure FL outcomes, which is supported by the broader health literacy studies. [74][75][76] Lastly, through this review we found that in recent years more studies addressed interactive and critical components of FL, reporting outcomes such as ''self-efficacy,'' ''behavioral intent,'' and ''attitudes,'' whereas the earliest studies were focused primarily on functional components (knowledge and skills). This may signal a shift in teaching practices toward more constructive approaches, or alternatively may relate to a purposeful recognition that successful asset acquisition requires higher-order FL skills.…”
Section: Discussionmentioning
confidence: 93%
“…Despite health knowledge improving in the majority of studies, not all demonstrate a change in health behaviors. 29 , 36 , 37 , 43 , 46 This finding of no significant change is supported by others, stating that knowledge alone will not lead to a change in behavior. 62 - 64 To change others’ behaviors, a HLM must be capable of promoting knowledge acquisition to enable individuals to autonomously make health-promoting decisions.…”
Section: Discussionmentioning
confidence: 70%
“… 61 , 71 Indeed, as shown in Table 3 , many of the studies did provide HL education during the childhood years, with a median age of 10 years. For example, Aghazadeh et al, 29 Hoare et al 42 and Wright et al 56 recommended that HL should be developed concurrently with childhood health behaviors. In contrast, papers by Bruselius-Jensen et al, 33 Greenberg et al 39 and Hughes and Maiden 43 suggest that adolescence is an appropriate life stage to implement HL education, as this is a key transition period into adulthood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation